Continuous, label-free, 96-well-based determination of cell migration using confluence measurement. Issue 1 (1st January 2019) - Mayr, Christian; Beyreis, Marlena; Dobias, Heidemarie; Gaisberger, Martin; Fuchs, Julia; Pichler, Martin; Ritter, Markus; Jakab, Martin; Helm, Katharina; Neureiter, Daniel; Kiesslich, Tobias
ABSTRACT: Cellular migration is essential in diverse physiological and pathophysiological processes. Here, we present a protocol for quantitative analysis of migration using confluence detection allowing continuous, non-endpoint measurement with minimal hands-on time under cell incubator conditions. Applicability was tested using substances which enhance (EGF) or inhibit (cytochalasin D, ouabain) migration. Using a gap-closure assay we demonstrate that automated confluence detection monitors cellular migration in the 96-well microplate format. Quantification by % confluence, % cell free-area or % confluence in cell-free area against time, allows detailed analysis of cellular migration. The study describes a practicable approach for continuous, non-endpoint measurement of migration in 96-well microplates and for detailed data analysis, which allows for medium/high-throughput analysis of cellular migration in vitro .